Efektivitas Terapi Kelompok Pendukung terhadap Kesejahteraan Subjektif pada Pasien HIV/AIDS - Tia Prasyatiani; Rr. Indahria Sulistyarini (Universitas Islam Indonesia, 2018)
This study aimed to determine the effect of support group therapy on subjective well-being in patients living with HIV / AIDS. Therapy with pretest-post-test design of the control and experimental groups was carried out in 3 meetings for approximately 1 week. Subjects in this study are patients living with HIV / AIDS. The experimental group (n = 3) is the group that received intervention in the form of support group therapy, while the control group (n = 3) as the waiting list group. This study used 2 scales to measure subjective well-being, which are Satisfaction With Life Scale (SWLS) to measure cognitive aspects and Positive And Negative Affect Scale (PANAS) to measure the affective aspects. The results of the study showed that support group therapy could increase the subjective well-being of patients living with HIV / AIDS.